Self-esteem of students diagnosed with adhd in schools from the city of Chillán, Chile - Carvajal Rojas, Camila (2020)
Objective: The objective was to measure the self-esteem of schoolchildren aged 8 to 13 diagnosed with ADHD. In private schools and municipal schools in the city of Chillán. Methodology: Quantitative, transversal methodology was used. The Marchant, Isabel Haeussler and Torretti School Self-Esteem Test (TAE) was applied. Results: At the end of the investigation, there was a significant difference between the self-esteem of students from subsidized and municipal private schools (p = 0.771), Fisher’s exact statistical test did not show a relationship between the variables of type of school and self-esteem (p = 0.597). The ANOVA test showed no relationship between the course variable and self-esteem (F = 0.400 p = 0.844). The T test showed a relationship between the variables self-esteem and sex (p = 0.039). Regarding the comparison by sex, it is observed that there is a significant difference in the self-esteem of men versus women, the former being the ones with the highest self-esteem, recommending strengthening self-esteem in the female population. Conclusions: It is recommended that there is a work of psycho-affective support, from the strengthening of the perception of self-esteem along with the inclusion of students with ADHD in all municipal schools and subsidized private schools in the city of Chillán. Emphasizing working with girls, who are diagnosed with ADHD, based on improving self-esteem along with the self-concept they perceive of themselves.